Development of a Career Awareness Board Game based on Augmented Reality for Generation Z Students - Bhakti, Caraka Putra; Ardiyanti, Difa; Kumara, Agus Ria; Ghiffari, Muhammad Alfarizqi Nizamuddin (Buletin Konseling Inovatif, 2025)
The purpose of this research is to develop an augmented reality-based career awareness board game for Generation Z students. The current development of the era demands that Generation Z have a good career. In reality, currently, there are still many Generation Z students in schools who do not have the skills, competencies, and awareness to have an optimal career. One important thing that Generation Z students need to have is career awareness. Having career awareness will help someone recognise their career needs based on their competencies, talents, and interests. Developing career awareness can be achieved through guidance and counselling services. Furthermore, to streamline the learning process, services also need to be supported by innovative media, including interactive media. board game. Board games are tools that can be designed and adapted to the needs and learning materials to be delivered. Furthermore, in this study, the designed board game is not only tailored to the material but also to technological developments. Therefore, augmented reality technology is incorporated to keep up with technological developments and the characteristics of Generation Z. The method in this study uses a research and development method with the Borg and Gall model, which is carried out up to the expert testing stage. The results of this study, the production of a board game that is safe and tested for validity by three experts and is said to be valid for use with the topic career awareness, from the validation test data, with an average of 0.83. In conclusion, the developed board game can be used as an alternative tool to increase career awareness. It is hoped that through board game, this can be an alternative tool in guidance and counselling services to develop career awareness of Generation Z students.